Carbon quantum dots modified tubular g-C3N4 with enhanced photocatalytic activity for carbamazepine elimination: Mechanisms, degradation pathway and DFT calculation - Chun Zhao; Zhenzhu Liao; Liu, Wen; Fuyang Liu; Jiangyu Ye; Jialiang Liang; Yunyi Li (Journal of Hazardous Materials, 2020)
A novel tubular graphitic carbon nitride (g-C3N4) modified with carbon quantum dots (CQDs) was fabricated and employed for the elimination of carbamazepine (CBZ) under visible light irradiation. The as-fabricated metal-free catalysts exhibited tubular morphologies due to the preforming of tubular protonated melamine with CQDs surface adsorption as the polymerization precursors. The surface bonded CQDs did not alter the band gap structure of g-C3N4, but greatly inhibited the charge recombination. Therefore, the CBZ degradation kinetics of tubular g-C3N4 were increased by over 5 times by the incorporation of CQDs. The main active species for CBZ degradation were found to be superoxide radical (O2−) and photo-generated holes (h+), which were further confirmed by electron spin resonance (ESR) analysis. In addition, the degradation pathways of CBZ were clarified via intermediates identification and quantum chemical computation using density functional theory (DFT) and wave function analysis. The olefinic double bond with the highest condensed Fukui index (f 0 = 0.108) in CBZ molecule was found to be the most preferable sites for radical attack. Moreover, good stability of the as-prepared photocatalysts was observed in the consecutive recycling cycles, while the slight decline of photocatalytic activity was attributed to the minimal surface oxidation.
Keywords: Carbamazepine; Carbon quantum dots; Photocatalytic degradation; Tubular carbon nitride; Visible light